2014
DOI: 10.1177/0040517513515320
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of energy usage in the hydroentanglement process

Abstract: The hydroentanglement process is highly energy intensive compared to other methods of manufacturing nonwoven fabrics. This paper presents an exploratory study on optimizing the usage of hydroentanglement energy so as to lower the processing cost. The experiments were based on a Box-Behnken experimental design (BBD) and multivariate linear regression analysis to model the tensile strength as response to variables. Three variables were selected, namely fabric area weight (150-400 g/m 2 ), machine speed (5-15 m/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The machine bonded the top and bottom sides of the cross-lapped batt successively in a single pass. 23 Nonwoven fabrics produced from two different fiber types, cotton (C) and viscose (V), were hydroentangled at different WJPs of 80 bar (P 1 ), 100 bar (P 2 ) and 120 bar (P 3 ).…”
Section: Nonwoven Fabric Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The machine bonded the top and bottom sides of the cross-lapped batt successively in a single pass. 23 Nonwoven fabrics produced from two different fiber types, cotton (C) and viscose (V), were hydroentangled at different WJPs of 80 bar (P 1 ), 100 bar (P 2 ) and 120 bar (P 3 ).…”
Section: Nonwoven Fabric Productionmentioning
confidence: 99%
“…This can be attributed to use of optimum WJP of 80 and 100 bar to form the two nonwoven fabrics as their areal weights are similar. Moyo et al 23 showed that for hydroentangled nonwoven fabrics, there is an optimum processing WJP beyond which the structural integrity of the fibers is adversely affected.…”
Section: Model and Experimental Micro-mechanical Behavior At Fabric Strain Of 10%mentioning
confidence: 99%
“…Generally higher jet energy produces fabrics with higher tensile strength, while reducing the fabric basis weight will affect the fabrics tensile property. Moyo et al [12] has undertaken a study for the optimization of the usage of energy during the hydroentanglement process. It should be important to note that there is a limit to the amount of energy used, since at some level, increase in higher energy may adversely affect the mechanical property of the fabric.…”
Section: Introductionmentioning
confidence: 99%